Photochemical preparation of (aza−)indolines: diastereoselective synthesis and polarity reversal strategy - Melder, Julian J.; Heldner, Maxi L.; Svetličić, Julia; Adow, Abdinasir; Rominger, Frank; Rudolph, Matthias; Helmchen, Günter; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2025)
Herein, we present the first light-mediated, diastereoselective de novo synthesis for 2,3-substituted indolines, a privileged scaffold in pharmaceuticals. The protocol was tested with various aryl and alkyl groups, maintaining high yields up to 85% across different substituents. The approach was further extended to enantioselective synthesis, yielding trans-2,3-substituted indolines with high enantiomeric excesses (94%-96% ee). Drawbacks resulting from low efficiencies for nucleophilic radicals in previous studies were addressed by a polarity reversal strategy, incorporating electron-withdrawing groups to improve the efficiency of the initial radical addition. Finally, the methodology was utilized for the synthesis of azaindolines, a highly valuable target in pharmaceutical research. Our approach now encompasses modifications to the aromatic backbone, the use of both nucleophilic and electrophilic radicals as coupling partners, the synthesis of indolines, azaindolines, and tetrahydroquinolines, variation of protecting groups, and the diastereoselective synthesis of 2,3-substituted indolines.